2004
DOI: 10.1111/j.1356-9597.2004.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of FGF target genes in Xenopus by microarray: temporal dissection of the signalling pathway using a chemical inhibitor

Abstract: Microarray is a powerful tool for analysing gene expression patterns in genome-wide view and has greatly contributed to our understanding of spatiotemporal embryonic development at the molecular level. Members of FGF (fibroblast growth factor) family play important roles in embryogenesis, e.g. in organogenesis, proliferation, differentiation, cell migration, angiogenesis, and wound healing. To dissect spatiotemporally the versatile roles of FGF during embryogenesis, we profiled gene expression in Xenopus embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…G protein-coupled receptors are known to transduce numerous extracellular signals into cells and regulate various aspects of cell proliferation (Marinissen and Gutkind, 2001). Recently, Gpr-4 was identified in a separate microarray experiment as a target gene for FGF signaling in Xenopus (Chung et al, 2004). In this study, Gpr-4 transcript was also observed in the endoderm and functional analysis of this gene revealed a potential role for Gpr-4 in regulating gastrulation movements (Chung et al, 2004).…”
Section: Gpr-4mentioning
confidence: 68%
See 2 more Smart Citations
“…G protein-coupled receptors are known to transduce numerous extracellular signals into cells and regulate various aspects of cell proliferation (Marinissen and Gutkind, 2001). Recently, Gpr-4 was identified in a separate microarray experiment as a target gene for FGF signaling in Xenopus (Chung et al, 2004). In this study, Gpr-4 transcript was also observed in the endoderm and functional analysis of this gene revealed a potential role for Gpr-4 in regulating gastrulation movements (Chung et al, 2004).…”
Section: Gpr-4mentioning
confidence: 68%
“…Recently, Gpr-4 was identified in a separate microarray experiment as a target gene for FGF signaling in Xenopus (Chung et al, 2004). In this study, Gpr-4 transcript was also observed in the endoderm and functional analysis of this gene revealed a potential role for Gpr-4 in regulating gastrulation movements (Chung et al, 2004). Gpr-4 also has oncogenic properties and has been shown to regulate pH and ERK activity (Sin et al, 2004;Ludwig et al, 2003;Bektas et al, 2003).…”
Section: Gpr-4mentioning
confidence: 72%
See 1 more Smart Citation
“…The way in which maternal determinants and FGF and nodal pathways cooperate to induce mesoderm has been examined in several ways, including analysis on arrays Smith, 2000, 2002;Chung et al, 2004). However, while a limited number of up-and down-regulated targets have been identified, we do not have a good understanding of how these signals cooperate to produce the final pattern of the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Many Wntinducible genes, including Cdx4, Xpo, Meis, and Marginal coil (Xmc), have been previously identified as FGF-responsive genes (Table 1) (Amaya et al 1993;Frazzetto et al 2002;Aamar and Frank 2004;Chung et al 2004;Keenan et al 2006). In studies using dominant-negative FGF receptor constructs and specific morpholino oligonucleotides, FGF signaling has been reported to be essential for the Wnt pathway to activate its targets during anteroposterior axis development (McGrew et al 1997;Maegawa et al 2006;Burks et al 2009).…”
Section: Cross Talk With Other Pathwaysmentioning
confidence: 99%